Growth model for morphological traits of buckwheat cultivars at sowing times - Marcos Vinícius Loregian; Alberto Cargnelutti Filho; Ismael Mario Márcio Neu; Valéria Escaio Bubans; Gabriel Elias Dumke; Felipe Manfio Somavilla (Revista Ciência Agronômica, 2024)
ABSTRACT The objective of this study was to fit the Logistic growth model for plant height and number of nodes of two buckwheat cultivars at sowing times, as well as comparing the cultivars and sowing times. Twenty uniformity trials were carried out, formed by the combination of two buckwheat cultivars (IPR91-Baili and IPR92-Altar), sown at five times, for two consecutive years. Evaluations were carried out twice a week throughout the vegetative stage until the end of flowering. In each evaluation, five plants were randomly collected from each trial to measure plant height and count the number of nodes on the main stem. The logistic model was fitted with the values of the five plants of each evaluation. Model parameters were estimated, as well as their respective confidence intervals. The goodness of fit of the model was assessed through the coefficient of determination, Akaike information criterion, and residual standard deviation. The plant height and number of nodes of buckwheat, cultivars IPR91-Baili and IPR92-Altar, were described by the Logistic model. The Logistic model satisfactorily describes the growth of buckwheat plants, and a specific fit considering each cultivar and sowing time is needed.